2011
DOI: 10.3109/1061186x.2011.589436
|View full text |Cite
|
Sign up to set email alerts
|

In vitroevaluation and biodistribution of HER2-targeted liposomes loaded with an125I-labelled DNA-intercalator

Abstract: The HER2-targeted liposomes possess the properties needed to bring about tumor-specific delivery and therapeutic effect of (125)I-Comp1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…A similar high tumor-specific cell killing potential has been established also for HER2-targeted Nuclisome-particles [33]. Further, data collected verified a dose-response correlation compatible with that expected following high linear energy transfer irradiation.…”
Section: Therapeutic Effect In Vitrosupporting
confidence: 76%
See 4 more Smart Citations
“…A similar high tumor-specific cell killing potential has been established also for HER2-targeted Nuclisome-particles [33]. Further, data collected verified a dose-response correlation compatible with that expected following high linear energy transfer irradiation.…”
Section: Therapeutic Effect In Vitrosupporting
confidence: 76%
“…By use of cellular assays that permitted quantification of the receptor-mediated uptake of the particles, we could confirm that the Nuclisome-particles are indeed taken up by the cultured cells through interaction with EGFR and HER2, respectively [32,33]. Importantly, the above studies showed that when receptors were blocked with an excess amount of free ligand, or liposomes were administered without targeting agent, the tumor-cell uptake was clearly suppressed.…”
Section: Target Specificitymentioning
confidence: 74%
See 3 more Smart Citations